Vitex Trifolia: A Review of Ethnobotany and Pharmacology - Gupta, Mohit Kumar; Tiwari, Gaurav; Gupta, Naveen; Rajput, Dharmendra (Journal of Neonatal Surgery, 2025)
Objective: From the point of view of this review, the following are some of the things that have been done or investigated with the plant Vitex trifolia habitat macro-microscopy, phytoconstituents, medicinal uses, clinical investigations, and toxicological. Methods: Many species of the genus Vitex are used extensively in traditional Indian medicine. There are 270 species of Vitex plants known to exist today. In Ayurveda and Unani, V. trifolia is used. Secondary metabolites, including tannins, saponins, polyphenolic chemicals, phytosterols, and terpenoids, are abundant in these plants. Results: The findings from different research Antiasthmatic, hepatoprotective, antibacterial, antioxidant, analgesic, larvicidal, and anti-inflammatory are some of the qualities possessed by V. trifolia. Conclusion: According to the V.trifolia review, further research into the plant's therapeutic value and the safety of its extracts is necessary.